A kink that makes you sick: the incentive effect of sick pay on absence - Böckerman Petri; Kanninen Ohto; Suoniemi Ilpo (Institute for the Study of Labor (IZA), 2022)
This paper examines the effect of the replacement rule of the Finnish sickness insurance
system on the duration of sickness absence. A pre-determined, piecewise linear policy rule in
which the replacement rate is determined by past earnings allows identification of the effect
using a regression kink design. We find a substantial and robust behavioral response. The
statistically significant point estimate of the elasticity of the duration of sickness absence with
respect to the replacement rate is on the order of 1.4.